Release of tumour necrosis factor alpha into bronchial alveolar lavage fluid following antigen challenge in passively sensitized guinea-pigs - D. E. Kelly; M. Denis; D. F. Biggs (Mediators of Inflammation)
Five groups of ten female guinea-pigs were passively sensitized against ovalbumin (OA) (n = 9) or control guinea-pig serum (n = 1). 24 h later, they received mepyramine (0.5 mg/kg, i.p.) and 30 min later inhaled aerosols of: (A) OA (2 in 0.9% saline, 8 min, n = 4/9); (B) saline (40 min, n = 4/9); (C) LPS (40 min, Escherichia coli 0111:B4, 150 ng/kg in PBS, n = 1/9); and (D) the control animal was treated as in (C) (n = 1). Their tracheas were cannulated under pentobarbital anaesthesia and bronchial alveolar lavage (BAL) was performed with 2 × 5 ml PBS containing BSA (1%) (n = 1 group), or BSA (1%) and aprotinin (1000 KIU/ml) (n = 4 groups), at 30, 60, 90 or 120 min post-inhalations. BAL fluids recovered were centrifuged, the supernatants recovered and frozen until assayed for tumour necrosis factor-α (TNF-α), interleukin-1 (IL-1) and interleukin-6 (IL-6). No TNF-α could be detected unless aprotinin was present in the lavaging solution. BAL fluid from OA-sensitized and control animals that had inhaled LPS contained high levels of TNF-α that peaked at 90 min. BAL fluid from OA sensitized animals that inhaled OA aerosols contained no detectable TNF-α at 30 min, but it was found in increasing amounts at 60, 90 and 120 min; TNF-α was not detected in fluid from any of the animals that inhaled saline. As BAL fluids were toxic to the cells used in the assays, neither IL-1 nor IL-6 could be measured. We conclude that the monokine TNF-α is released into BAL fluid following anaphylactic challenge of passively sensitized guinea-pigs. The presence of the antiprotease, aprotinin, in the lavaging solution is essential for the detection and measurement of TNF-α in BAL fluid.